2005 IEEE Congress on Evolutionary Computation
DOI: 10.1109/cec.2005.1555046
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Internal and External Metrics in Co-evolution

Abstract: Co-evolutionary algorithms (CEAs) have been applied to optimization and machine learning problems with often mediocre results. One of the causes for the unfulfilled expectations is the discrepancy between the external problem solving goal and the internal mechanisms of the algorithm. In this paper, we investigate in a principled way the relationships between the internal subjective metric used as fitness by a co-evolutionary algorithm and the external objective metric measuring the algorithm's progress towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…This technique was first introduced in (Popovici and De Jong, 2004) and has been improved since then. We have already successfully used it to gain insight into the way co-evolutionary algorithms work, both in competitive (Popovici and De Jong, 2005b) and cooperative setups (Popovici and De Jong, 2005a;Popovici and De Jong, 2005c). In this paper we describe this technique and use it to extend our previous results.…”
Section: The Importance Of Co-evolutionary Dynamicsmentioning
confidence: 87%
See 1 more Smart Citation
“…This technique was first introduced in (Popovici and De Jong, 2004) and has been improved since then. We have already successfully used it to gain insight into the way co-evolutionary algorithms work, both in competitive (Popovici and De Jong, 2005b) and cooperative setups (Popovici and De Jong, 2005a;Popovici and De Jong, 2005c). In this paper we describe this technique and use it to extend our previous results.…”
Section: The Importance Of Co-evolutionary Dynamicsmentioning
confidence: 87%
“…Additionally, although this paper has focused on cooperative setups, our previous work (Popovici and De Jong, 2004;Popovici and De Jong, 2005b) showed that the methods described here can be used to gain insights into competitive co-evolution as well.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their similarity in framework, co-evolutionary learning and EAs are fundamentally different in how the fitness of a solution is assigned, leading to significantly different outcomes when applied to similar problems (e.g., different search behaviors on the space of solutions [7,8]). EAs are often viewed and constructed in terms of an optimization context [4,5], whereby an absolute fitness function is required to assign the fitness value to a solution that is objective (fitness value for a solution is always the same regardless of the context).…”
Section: Introductionmentioning
confidence: 99%
“…For such problems, continued use of an inappropriate fitness function will often bias the search to solutions that do not reflect the underlying properties of the problem, leading to suboptimal solutions [12]. Even if a fitness function can be formulated, it may not be able to evaluate and differentiate between individual solutions to provide some gradient to direct the search when using EAs [8,13]. One such problem that is difficult to solve using EAs, but can be naturally framed in co-evolutionary learning, is the problem of game-playing [2,3,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, early coevolutionary learning systems are implemented using coevolutionary algorithms derived from EAs [11], [13]. However, coevolutionary learning and EAs are fundamentally different in how the fitness of a solution is assigned, which may lead to significantly different outcomes when they are applied to similar problems (different search behaviors on the space of solutions) [14], [15]. Classical EAs are formulated in the context of optimization [3], [5], [6], where an absolute fitness function is used to assign fitness values to solutions.…”
mentioning
confidence: 99%